2003
DOI: 10.1149/1.1543949
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Metallic Lithium Toward γ-Butyrolactone, Propylene Carbonate, and Dioxalane

Abstract: The nature of the reaction products generated by exposure of a model cyclic ester, ␥-butyrolactone ͑␥-BL͒, two cyclic ethers, dioxalane ͑DIOX͒ and tetrahydrofuran ͑THF͒, and a cyclic alkyl carbonate, propylene carbonate ͑PC͒, toward metallic Li at room temperature was examined in ultrahigh vacuum by infrared reflection absorption, Auger electron ͑AES͒, and X-ray photoelectron ͑XPS͒ spectroscopies. The features observed in the spectra were consistent with Li butyrate and Li ␤-keto ester in the case of ␥-BL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Among the limited choices of candidates intended to replace cyclic carbonates, γ-butyrolactone (γBL) seemed to be the most promising and therefore closest to practical application. γBL has long been considered a possible component for electrolytes in lithium/lithium ion cells due to its moderately high dielectric constant, relatively low viscosity, EC-like structure, and excellent solvating ability. Its reductive behavior has been studied on inert electrode surfaces, , lithium surfaces, , and graphite surfaces . Unfortunately, in the early era of lithium ion technology, Aurbach and co-workers had found that γBL/LiAsF 6 solution failed to perform satisfactorily in lithium ion cells based on the graphite anode unless under an atmosphere of CO 2 , thus diminishing its possible application .…”
Section: 31 Nonaqueous Solventsmentioning
confidence: 99%
“…Among the limited choices of candidates intended to replace cyclic carbonates, γ-butyrolactone (γBL) seemed to be the most promising and therefore closest to practical application. γBL has long been considered a possible component for electrolytes in lithium/lithium ion cells due to its moderately high dielectric constant, relatively low viscosity, EC-like structure, and excellent solvating ability. Its reductive behavior has been studied on inert electrode surfaces, , lithium surfaces, , and graphite surfaces . Unfortunately, in the early era of lithium ion technology, Aurbach and co-workers had found that γBL/LiAsF 6 solution failed to perform satisfactorily in lithium ion cells based on the graphite anode unless under an atmosphere of CO 2 , thus diminishing its possible application .…”
Section: 31 Nonaqueous Solventsmentioning
confidence: 99%